Implementasi Sistem Monitoring Keamanan Rumah Pintar Berbasis Alexa Voice Command Pada Raspberry Pi - Bramantyo Ardi; Sabriansyah Rizqika Akbar; Rizal Maulana (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2019)
Smart home is a house that provides comfort, safety and convenience to its inhabitants. A few years ago this smart home technology has grown very rapidly. There are several methods in its development, one of which is using voice control method. One of the emerging Voice Control System technologies is the Alexa Voice Service developed by Amazon. In this research will be implementing Alexa Voice Service on Raspberry Pi devices that can control some sensors that will be implemented on a smart home. The commands to be used on Raspberry Pi devices will be delivered to the Alexa Skills Kit via the Alexa Web Service already installed on Raspberry Pi devices. Then the command will be sent to Amazon Web Service Lambda and then modeled with JSON format so that voice commands can be recognized by the system. Then the formatted sensor data will be published to MQTT. Furthermore, Alexa Web Service Lambda will subscribe data that later data will be voiced by Alexa. The accuracy of the sound system to read sensor data reaches 80 %.